2019
DOI: 10.1080/08856257.2019.1703548
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality in special education: a meta-analysis of single-subject design studies

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 56 publications
3
43
0
1
Order By: Relevance
“…Findings indicate that AR technology is an effective instructional strategy for teaching a multitude of behaviors in real-world settings for children and adolescents with autism [ 14 ]. AR applications can contribute to the way individuals with ASD learn daily life skills as well as can facilitate individuals’ understanding of social communicative behavior, enhancing attentional capacities and contributing to the recognition of facial emotions, among other advantages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings indicate that AR technology is an effective instructional strategy for teaching a multitude of behaviors in real-world settings for children and adolescents with autism [ 14 ]. AR applications can contribute to the way individuals with ASD learn daily life skills as well as can facilitate individuals’ understanding of social communicative behavior, enhancing attentional capacities and contributing to the recognition of facial emotions, among other advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified the advantages provided by computerized learning of different functional and social skills [ 11 , 14 ]. Specifically, among the strengths of the use of technology in interventions addressed at children with ASD, the possibility to clearly define tasks, to keep the focus of attention, to minimize distractions, and to facilitate personal skills and strategies with a tool that can be used for many applications is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with ADHD can be grouped based on symptoms with one group showing inattention only, another hyperactivity or impulsiveness and then a group which evidences all the symptoms [6]. Several studies have been reported in literature on the relationship between computer technologies and learning process of children with ADHD, including improving the learning and skill acquisition of individuals with special needs [7], improving ADHD individuals' executive functions through [6], and engaging children with ADHD using Sifteo cubes technology [8].…”
Section: Introductionmentioning
confidence: 99%